Prognostic factors for employment outcomes in patients with a history of childhood-onset drug-resistant epilepsy - Arai, Yuto; Okanishi, Tohru; Noma, Hisashi; Kanai, Sotaro; Kawaguchi, Tatsuya; Sunada, Hiroshi; Fujimoto, Ayataka; Maegaki, Yoshihiro (Frontiers in Pediatrics, 2023)
Objective: The employment outcomes of childhood-onset drug-resistant epilepsy (DRE) has not been studied enough. The aim of this retrospective cohort study is to investigate the employment outcomes of childhood-onset DRE in June 2022 and identify the risk factors associated with non-employment. Materials and methods: The sample consisted of 65 participants ≥18 years of age with a history of childhood-onset DRE. Fifty participants (77%) were salaried employees and 15 participants (23%) were non-employed. Clinical and psychosocial information were evaluated for calculating the relative risk (RR) of non-employment. Results: Regarding medical factors, lower IQ (RR, 0.645; 95% confidence interval [CI], 0.443–0.938; p=0.022) was positively associated with employment. In contrast, age at follow-up (RR, 1.046; 95% CI, 1.009–1.085; p=0.014); number of ASMs at follow-up (RR, 1.517; 95% CI, 1.081–2.129; p=0.016); use of medications such as phenobarbital (RR, 3.111; 95% CI, 1.383–6.997; p=0.006), levetiracetam (RR, 2.471; 95% CI, 1.056–5.782; p=0.037), and topiramate (RR, 3.576; 95% CI, 1.644–7.780; p=0.001) were negatively associated with employment. Regarding psychosocial factor, initial workplace at employment support facilities (RR, 0.241; 95% CI, 0.113-0.513; p<0.001) was positively associated with employment. In contrast, complication of psychiatric disorder symptoms (RR, 6.833; 95% CI, 2.141–21.810; p=0.001) was negatively associated with employment. Regarding educational factor, graduating schools of special needs education (RR, 0.148; 95% CI, 0.061–0.360; p<0.001) was positively associated with employment. Conclusions: Specific medical, psychosocial, and educational factors may influence the employment outcomes of childhood-onset DRE. Paying attention to ASMs’ side effects, adequately preventing the complications of psychiatric disorder symptoms, and providing an environment suitable for each patient condition would promote a fine working status for people with childhood-onset DRE.